2018
DOI: 10.1007/s40565-018-0435-z
|View full text |Cite
|
Sign up to set email alerts
|

A learning framework based on weighted knowledge transfer for holiday load forecasting

Abstract: Since the variation pattern of load during holidays is different than that of non-holidays, forecasting holiday load is a challenging task. With a focus on this problem, we propose a learning framework based on weighted knowledge transfer for daily peak load forecasting during holidays. First, we select source cities which can provide extra hidden knowledge to improve the forecast accuracy of the load of the target city. Then, all the instances which are from source cities and the target city will be weighted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In addition, it is found that some special days affect load trends rapidly in a short period based on the above analysis, which is also confirmed in the previous work [28], [32]. Accordingly, special days must be considered as an important factor in STLF, especially Chinese national legal holidays listed in Table 1.…”
Section: Features Selectionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition, it is found that some special days affect load trends rapidly in a short period based on the above analysis, which is also confirmed in the previous work [28], [32]. Accordingly, special days must be considered as an important factor in STLF, especially Chinese national legal holidays listed in Table 1.…”
Section: Features Selectionsupporting
confidence: 83%
“…It is easy that only 5 missing points are supplemented by linear interpolation because of that there is only one missing point in every breaking interval. Then, Pauta criteria [27] are used to identify outliers, which is similar to [28]. Assume x i is sample data set during a period of time, the process of detecting outlier by Pauta criteria can be listed as follows:…”
Section: A Data Preprocessingmentioning
confidence: 99%
“…Natural factors include temperature, air pressure, weather, air quality, etc., and social factors include holidays, weekdays, GDP, etc. These factors are widely used as feature variables [22]- [24]. Additionally, the current load variation is closely related to the historical load.…”
Section: A Dataset Collection and Splittingmentioning
confidence: 99%
“…Figure 18 explains the scenario of flexible and not flexible resources where the horizontal-axis represents cumulative quantity supplied in MWh, and the vertical-axis means the marginal cost in $/MWh. As has been seen, oil, in general, is costly and suggested not to use until it is of absolute necessity [89], [90].…”
Section: B Load Forecasting Techniquesmentioning
confidence: 99%